Radical interstitial HDR brachytherapy in treatment of recurrent vulvar cancer: a case study - Kellas-Ślęczka, Sylwia; Białas, Brygida; Wojcieszek, Piotr; Fijałkowski, Marek; Szlag, Marta; Cholewka, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2012)
Background : Recurrences in vulvar cancer are a very important problem. It is estimated that even in multimodality treatment, about 10-20% of patients with the early stage and 50-70% with the advanced disease will develop recurrences. Interstitial High Dose Rate (HDR) Brachytherapy as a “boost” or as a sole treatment is one of the possible techniques in local failures in vulvar cancer therapy. Case report: We report a case of a vulvar cancer local recurrence in a 90-year-old patient after primary surgery who was treated successfully and radically with interstitial HDR brachytherapy. Conclusion : Interstitial HDR Brachytherapy in selected patients with a vulvar cancer local recurrence is an effective and safe method which allows to preserve organ functions with good cosmetic results.